Evaluation of the best solution for the functionalization of photocatalytic, superhydrophobic, and self-cleaning properties on asphalt mixtures - Rocha Segundo, Iran Gomes da (2021)
This research aims to develop asphalt mixtures with new capabilities with photocatalytic, superhydrophobic, and self-cleaning capabilities. Different solutions were prepared combining nano-TiO2 and micro-PTFE on water, and ethyl alcohol and dimethyl ketone with different concentrations. The solutions were sprayed over the asphalt mixtures and the new capabilities were evaluated via decolourization of Rhodamine B dye aqueous solution under simulated solar irradiation and Water Contact Angle measurements. Among the combinations analysed, the best solution was TiO2 PTFE with ethyl alcohol (8 g/L).